Long-Term Cardiac Damage Associated With Abdominal Irradiation in Mice - Wang, Zhaojia; Jia, Ziheng; Zhou, Zandong; Zhao, Xiaotong; Wang, Feng; Zhang, Xu; Tse, Gary; Li, Guangping; Liu, Yang; Liu, Tong (Frontiers in Pharmacology, 2022)
Aims Irradiation is an effective treatment for tumors but has been associated with cardiac dysfunction. However, the precise mechanisms remain incompletely elucidated. This study investigated the long-term cardiac damage associated with abdominal irradiation and explored possible mechanisms. Methods and Results Wild-type C57BL6/J mice were divided into two groups: untreated controls (Con) and treatment group receiving 15 Gy of abdominal gamma irradiation (AIR). Both groups received normal feeding for 12 months. The AIR group showed reductions in left ventricular ejection fraction (LVEF), fractional shortening (FS), left ventricular end-diastolic internal diameter (LVID; d), left ventricular end- diastolic volume (LV Vol. diastolic volume (LV Vol; d) and mitral transtricuspid flow late diastolic filling velocity (MV A). It also showed increased fibrosis, reduced conduction velocity and increased conduction heterogeneity. Non-targeted metabolomics showed the differential metabolites were mainly from amino acid metabolism. Further KEGG pathway annotation and enrichment analysis revealed that abnormalities in arginine and proline metabolism, lysine degradation, d-arginine and d-ornithine metabolism, alanine, aspartate and glutamate metabolism, and arginine biosynthesis. Conclusion Abdominal irradiation causes long-term damage to the non-irradiated heart, as reflected by electrical and structural remodeling and mechanical dysfunction associated with abnormal amino acid biosynthesis and metabolism.